2023
DOI: 10.1038/s41467-023-37825-x
|View full text |Cite|
|
Sign up to set email alerts
|

Expansion of circulating stem-like CD8+ T cells by adding CD122-directed IL-2 complexes to radiation and anti-PD1 therapies in mice

Abstract: Combination of radiation therapy (RT) with immune checkpoint blockade can enhance systemic anti-tumor T cell responses. Here, using two mouse tumor models, we demonstrate that adding long-acting CD122-directed IL-2 complexes (IL-2c) to RT/anti-PD1 further increases tumor-specific CD8+ T cell numbers. The highest increase (>50-fold) is found in the blood circulation. Compartmental analysis of exhausted T cell subsets shows that primarily undifferentiated, stem-like, tumor-specific CD8+ T cells expand in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…The combination of RT and modified IL-2 variants has achieved potent anti-cancer responses in both preclinical models as well as in clinical trials and is proving to be an efficacious therapeutic combination 32,33,60 . However, a majority of these IL-2 variants target the dimeric IL-2R to stimulate memory CD8 + T cells and avoid Treg expansion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of RT and modified IL-2 variants has achieved potent anti-cancer responses in both preclinical models as well as in clinical trials and is proving to be an efficacious therapeutic combination 32,33,60 . However, a majority of these IL-2 variants target the dimeric IL-2R to stimulate memory CD8 + T cells and avoid Treg expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RT was combined with IL-2 variants that preferentially targeted effector immune cells or antigens present in the tumor microenvironment [30][31][32][33] . Although these studies demonstrated some efficacy of combined RT and IL-2 immunotherapy, it is unknown which IL-2R signals and bias combine best with which RT treatment scheme.…”
Section: Introductionmentioning
confidence: 99%
“… 532 However, several recent papers reported less terminal exhaustion, and expansion of stem-like and effector-like T cells upon treatment with IL-2 or IL-2 variants. 379 , 533 , 534 When recombinant wild-type IL-2 was combined with PD-1 blockade in the model of chronic lymphocytic choriomeningitis virus infection, even a deviation from the normal exhaustion program towards the formation of “better effectors” was observed and depended on IL-2 binding to CD25. 534 , 535 Similar observations were made in tumor models using an IL-2Rβγ-biased IL-2 derivative fused to an anti-PD-1 antibody.…”
Section: Cytokinesmentioning
confidence: 99%
“…Moreover, TA-HEVs have recently been associated with a higher proportion of TCF1 + TIM3 - PD1 + stem-like exhausted CD8 + tumor-infiltrating lymphocytes (TILs) 28 . These TCF1 + PD1 + cells differentiate into the effector-like “transitory” CD101 - TIM3 + PD1 + subset originally described in the model of lymphocytic choriomeningitis virus (LCMV) 29 and later found in mouse tumor models 30 . Terminally differentiated exhausted T cells exhibit expression of CD101 and decreased cytokine production 29 - 31 .…”
Section: Introductionmentioning
confidence: 97%
“…Terminally differentiated exhausted T cells exhibit expression of CD101 and decreased cytokine production 29 - 31 . Non-terminally differentiated exhausted CD8 + T cells were reported to positively correlate with favorable anti-tumor response following immunotherapy 32 , 33 or radio/immunotherapy 30 , 34 , 35 .…”
Section: Introductionmentioning
confidence: 99%